ANALISIS DAN PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG PADA TOKO XYZ - Gani, Alcianno G. (Universitas Dirgantara Marsekal Suryadarma, 2022)
The Inventory Information System in XYZ Store still uses the manual method, namely by recording books. With the creation of a Web-based Inventory Information System, it is hoped that it can assist in managing inventory and provide accurate information for users. This Goods Inventory Information System can assist in managing inventory, providing detailed information on the purchase of goods, demand for goods and report data on purchases of goods and requests for goods. This inventory information system is designed and built using the PHP programming language and MySQL database.Â Keywords: Inventory of goods, Purchase of Goods, Demand for goods, Information System, PHP, MySQL.